2007
DOI: 10.3748/wjg.v13.i6.970
|View full text |Cite
|
Sign up to set email alerts
|

Stent placement is effective on both postoperative hepatic arterial pseudoaneurysm and subsequent portal vein stricture: A case report

Abstract: To treat postoperative bleeding after hepato-pancreatobiliary surgery, interventional radiology has become essential. We report a case of coincidental pseudoaneurysm and jejunal varices that were both successfully treated by stent-grafts. After a pancreaticoduodenectomy, the patient developed a pseudoaneurysm in the hepatic artery and a stenosis in its periphery. After establishing hepatic arterial flow by placing stent-grafts over both the pseudoaneurysm and the stenosis, the pseudoaneurysm was embolized with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Recently, hemostatic treatment using stent‐grafts has been reported ,. The placement of a polytetrafluoroethylene (PTFE) covered stent can be used both for hemostasis from pseudoaneurysms and to preserve the patency of the hepatic artery.…”
Section: Stent‐graft Placement As a Novel Strategy For Intraabdominalmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, hemostatic treatment using stent‐grafts has been reported ,. The placement of a polytetrafluoroethylene (PTFE) covered stent can be used both for hemostasis from pseudoaneurysms and to preserve the patency of the hepatic artery.…”
Section: Stent‐graft Placement As a Novel Strategy For Intraabdominalmentioning
confidence: 99%
“…Recently, hemostatic treatment using stent-grafts has been reported. 15,[31][32][33][34][35] The placement of a polytetrafl uoroethylene (PTFE) covered stent can be used both for hemostasis from pseudoaneurysms and to preserve the patency of the hepatic artery. The placement of these stents is technically challenging with the currently avail-able stent-graft devices, which vary from 2.5 mm to 6 mm in diameter, [31][32][33][34][35] but the use of these stents offers an alternative for situations in which the collateral hepatic arterial supply is insuffi cient or the portal vein is compromised.…”
Section: Stent-graft Placement As a Novel Strategy For Intraabdominalmentioning
confidence: 99%
“…[8][9][10][13][14][15][16][17][18][19].Olcott et al reported the first case after liver transplantation in 1990 [20], and Hiraoka et al reported the first case of PV stenosis after PD in 2001…”
mentioning
confidence: 99%
“…In cases of postsurgical biliary PA, SEMS placement is reported to be an effective treatment (21, 22). Cases of post-stenting PA all develop biliary bleeding, so a covered SEMS might be a useful tool for achieving pressure hemostasis and may be a viable treatment choice.…”
Section: Discussionmentioning
confidence: 99%